Influence of Ploidy Levels on Phenotypic and Cytogenetic Traits in Maize and Zea perennis Hybrids - Molina, María del Carmen (1999)
The aim of this work was to analyse: a) the phenotypic and cytogenetic differences of Zea mays and Zea perennis hybrids 2n=30 and 40; b) the effect of colchicine on their chromosomes pairing in meiosis. The plant materials used for these studies were Z. mays (Zm20) 2n=20, Z. mays (Zm40) 2n=40 and Z. perennis (Zp) 2n=40 and the hybrids Zm20 ×Zp (MP30) 2n=30 and Zm40 × Zp (MP40) 2n=40. Some characteristics of Z. perennis such as rhizomes, distic ears, perennially and profuse tillering were only observed in MP40 plants. In the other hand, MP30 plants had maize like phenotype; they were annual, with 4 round ears and low tillering. Therefore, phenotypic expression of several traits depends upon the dose of genes from each parent in the hybrid. The genomic formulae proposed for these species and hybrids were Zm20: AmAm BmBm; Zm40: AmAmAmAm BmBmBmBm; Zp: ApApApAp Bp1Bp1 Bp2Bp2; MP30: AmApAp Bp1Bp2 Bm; MP40: AmAmApAp BmBm Bp1Bp2. Prezigotene colchicine treatment increased the frequency of quadrivalents in Zm20, Zp and Mp40 and trivalents in MP30. These results suggest homoeology between Bm and Bp1Bp2 genomes from maize and Zp, respectively.